Catzonia World / Siti Nur Syafiqah Mohd Johari - Mohd Johari, Siti Nur Syafiqah (2020)
Catzonia is a sole proprietorship company that can be categorized as Small Medium Enterprise (SME) which provide cat products to the customers especially to the cat owners. For now, we are focusing to introduce a new pet product called “Kitty Litty Smart Scoop Litter Box”. It is an auto-self cleaning litter box equipped with sensor that can detect and clean the cat waste itself. Our product is user-friendly and easy to use. Our company have the ability to offer highest possible quality pet products and services at lowest shocking price.